Meaning – Quest for Meaning – Meaning of Life (I) - Wagner, Harald (Acta Paedagogica Vilnensia, 2006)
This is the first of the four articles that constitute the cycle dedicated to the issues of meaning, quest for meaning, and meaning of life. The question of the meaning of life is the concern of modern humans. This concern expresses the loss of orientation, search for security and successful life. There are many answers in various fields proposed to the question of the meaning of life, however often these discussions and deliberations take place without defining the concepts and the basis of thought. This article attempts to overview the ongoing discussion, define the limits of the investigation of the meaning of life,